TI_GERICHTE 15.2006.33 vom 24. April 2006 , Comminatoria di fallimento. Mancanza di liquidità. Potere di apprezzamento. - TI Tribunale d'appello (2006)
Comminatoria di fallimento. Mancanza di liquidità. Potere di apprezzamento.